Hubungan Stres, Kualitas Tidur dan Aktivitas Fisik terhadap Kejadian Migrain Mahasiswa FK UNRAM Angkatan 2021 - Bintang Alif Najih Hidayat; I Wayan Tunjung; Muhammad Ashhabul Kahfi Mathar; Rohmania Setiarini (Syntax Corporation Indonesia, 2024)
The purpose of this study was to determine the relationship between stress, sleep quality and physical activity with the incidence of migraines in students of the Faculty of Medicine, University of Mataram (FK UNRAM) class of 2021. This study is a type of observational analytical quantitative research with a cross-sectional study design. This approach is done by looking for the relationship between the independent variable (exposure or risk factor) and the dependent variable (effect or effect) with data collection only done once at the same time. From the description above, it can be concluded that research on the relationship between stress, sleep quality, and physical activity with the incidence of migraines in students of the class of 2021 Faculty of Medicine, University of Mataram, results show that the prevalence of students who do not experience migraines is 80.0%, those who do not experience stress by 50.0%, who have good sleep quality by 71.7%, and who have moderate physical activity by 45.0%.